Scapular movement training versus standardized exercises for individuals with chronic shoulder pain: protocol for a randomized controlled trial - Kamonseki D.H. (2021)
© 2020 Associação Brasileira de Pesquisa e Pós-Graduação em FisioterapiaBackground: Scapular focused exercise interventions are frequently used to treat individuals with shoulder pain. However, evidence for changes in scapular motion after intervention is limited. Objective: To compare the effects of scapular movement training versus standardized exercises for individuals with shoulder pain. Methods: This will be a single-blinded randomized controlled trial. Sixty-four individuals with shoulder pain for at least 3 months, scapular dyskinesis, and a positive scapular assistance test will be randomly allocated to one of two groups: Scapular Movement Training (group 1) and Standardized Exercises (group 2). Group 1 will receive education about scapular position and movement, and be trained to modify the scapular movement pattern. Group 2 will perform stretching and strengthening exercises. Both groups will be treated twice a week for eight weeks. Three-dimensional scapular kinematics and muscle activity of the serratus anterior and upper, middle, and lower trapezius during elevation and lowering of the arm will be assessed at baseline and after 8 weeks of treatment. Pain intensity, function, fear avoidance beliefs, and kinesiophobia will be assessed at baseline and after 4 and 8 weeks of treatment, and 4 weeks after the end of treatment. Conclusions: The results of this study may contribute to a better understanding of the efficacy of scapular focused treatments for individuals with shoulder pain. Clinical trial registration: NCT03528499